Complete male mitochondrial genomes of European Mytilus edulis mussels. (3rd May 2016) - Śmietanka, Beata; Wenne, Roman; Burzyński, Artur
Abstract: Doubly uniparental inheritance (DUI) results in the existence of two gender-specific, divergent mtDNA lineages within a single species. Under DUI, the female genome (F) is transmitted from mothers to the whole offspring, and the male genome (M) is transmitted exclusively from fathers to sons. This system was first described in a marine mussels Mytilus edulis inhabiting European coastal waters, over a decade ago. Despite that, the complete sequence of the M genome from the European M. edulis mussels remained unknown. Here we announce it for the first time. The announcement is based on the two haplotypes isolated from heteroplasmic males of European M. edulis sampled at two moderately distant locations: southern North Sea and western Baltic. The two M genomes are quite similar both in length (16, 631 and 16, 632 bp) and in sequence (98.3%). Furthermore, both newly sequenced genomes are closely related to the genomes described from Baltic M. trossulus .